1999
DOI: 10.1002/1529-0131(199912)42:12<2674::aid-anr25>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Temporal artery biopsy: A diagnostic tool for systemic necrotizing vasculitis

Abstract: Objective. To describe the clinical, biologic, and histologic features of temporal artery biopsy (TAB)-localized systemic necrotizing vasculitides (SNV), and to assess their frequency among elderly patients undergoing TAB for suspected giant cell (temporal) arteritis (GCA).Methods. The frequency of a TAB localization of SNV was prospectively assessed in a multicenter study of elderly patients undergoing TAB for suspected GCA. All patients with SNV fulfilling the American College of Rheumatology criteria for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 44 publications
2
51
0
11
Order By: Relevance
“…[55][56][57][58] It has been suggested that TAB may be a useful test to diagnose other forms of vasculitis, which could mimic GCA. 59 There is an inevitable tension between obtaining enough material to make a diagnosis and initiating therapy before disease-related complications set in. In practice, it is common for patients to start on treatment as soon as a physician suspects the diagnosis, typically based on symptoms suggesting the diagnosis of GCA and possible laboratory investigations such as an elevated C-reactive protein (CRP) level or ESR.…”
Section: Diagnosis Of Giant Cell Arteritis Relying On a Gold Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58] It has been suggested that TAB may be a useful test to diagnose other forms of vasculitis, which could mimic GCA. 59 There is an inevitable tension between obtaining enough material to make a diagnosis and initiating therapy before disease-related complications set in. In practice, it is common for patients to start on treatment as soon as a physician suspects the diagnosis, typically based on symptoms suggesting the diagnosis of GCA and possible laboratory investigations such as an elevated C-reactive protein (CRP) level or ESR.…”
Section: Diagnosis Of Giant Cell Arteritis Relying On a Gold Standardmentioning
confidence: 99%
“…11,115 Patients who had a positive biopsy but who did not have GCA were reported to have other forms of vasculitis. 59 We wanted to compare the performance of ultrasound, which we predicted would provide 87% sensitivity and 83% specificity or higher. Among 381 patients who had ultrasound and TAB for suspected GCA, 101 (27%) had a TAB consistent with GCA and 162 (43%) had an ultrasound result compatible with GCA.…”
Section: Main Findingsmentioning
confidence: 99%
“…The classic histologic picture of GCA is characterized by panarteritis with a predominantly lymphomononuclear inflammatory cell infiltrate, with or without giant cells [5]. Recently, however, it has been demonstrated that together with transmural involvement, the inflammation may be restricted to the vasa vasorum (vasa vasorum vasculitis, VVV), to the periadventitial small vessels (small vessel vasculitis, SVV), or both [12].…”
Section: Histologic Heterogeneity In Gca Arteriesmentioning
confidence: 99%
“…In many patients a systemic inflammatory response may also occur with fever, weight loss and fatigue [2]. To date no specific circulating biomarkers have been identified and the gold standard for the diagnosis of GCA remains the biopsy of temporal artery (TAB) [3][4][5]. Histologically, arteries show inflammation and necrosis of the arterial media wall, infiltrating CD4 + T lymphocytes, macrophages multinucleated giant cells and/or epithelioid macrophages with the production of various cytokines and arterial remodelling [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, his relatively young age and months of ocular symptoms without progression to blindness make GCA less likely. Antineutrophil cytoplasmic antibody-associated vasculitis and other primary forms of vasculitis can also affect the temporal arteries and mimic GCA and PMR (3,4). However, the patient lacks any features of a systemic small-or medium-vessel vasculitis.…”
Section: Ischemic Etiologiesmentioning
confidence: 99%